Gain development and evaluation of a trajectory / path control design using nonlinear dynamic inversion = Verstarkungsauslegung und evaluation eines trajektorien- / pfadregelungsansatzes basierend auf ein-ausgangs-linearisierung - Bharathkumar, Balaji (2016)
This report discusses the design of gains for an outer Ioop trajectory error controller employing stability and performance requirements. A short review on trajectory control for automatic applications carried out in the past is presented at the beginning. Since the controller discussed in this report is based on the control methodology Nonlinear Dynamic Inversion, a chapter explaining the principles of Nonlinear Dynamic Inversion along with mathematical formulations is presented, followed by a brief description on the application of this theory to the trajectory controller. The mathematical formulation of two classes of transfer functions is explained subsequently with the motive. A chapter on trajectory creation is followed up next, which discusses the creation of a reference trajectory, which forms the basis for the gain design process of the outer Ioop trajectory controller. The algorithms used for the gain design process of this controller are explained- in detail, highlighting the simulation model and performance requirements involved in the design process. The discussion on the shortlisted set of gains and the performance of the controller for those gains are presented in the final chapter. Finally this report concludes with the objectives achieved in this thesis along with few shortcomings involved in the process and plan for future work.